Music Business and the Experience Economy The Australasian Case - Tschmuck, Peter.; Tschmuck, Peter.; Pearce, Philip L.; Pearce, Philip L.; Campbell, Steven.; Campbell, Steven. (Springer Berlin Heidelberg : Imprint: Springer, 2013)
Music Business and the Experience Economy is the first book on the music business in Australasia from an academic perspective. In a cross-disciplinary approach, the contributions deal with a wide-range of topics concerning the production, distribution and consumption of music in the digital age. The interrelationship of legal, aesthetic and economic aspects in the production of music in Australasia is also highlighted as well as the emergence of new business models, the role of P2P file sharing, and the live music sector. In addition, the impact of the digital revolution on music experience and valuation, the role of music for tourism and for branding, and last but not least the developments of higher music education, are discussed from different perspectives.